A GLOBAL GENE EXPRESSION APPROACH TO EXPLORING ROCK COLONIZATION BY BLASTOCOCCUS SAXOBSIDENS - Wilmot, Ryan Patrick (University of New Hampshire Scholars' Repository, 2023)
Introduction: Blastococcus saxobsidens is an endolithic bacterium associated with biodegradation of stone monuments across the Mediterranean basin. Recently, strains of the bacterium have been isolated from high altitude deserts in Chile, volcanic glass in Iceland, and from masonry of several cultural heritage sites across Europe and the Americas. Blastococcus saxobsidens global dispersion has been linked to patterns of wind distributed dust particles. The physiology that this bacterium uses to colonize a wide range of rock types in such distinct locations has not been previously explored however. This project has established that B. saxobsidens colonizes and respires a variety of chemically distinct rock types. An RNAseq approach was used to capture their transcriptome during rock colonization. The resulting profiles, which represent snapshots of global gene expression, were compared to the profile of B. saxobsidens cells grown in liquid Czapek broth without rocks. The differential gene expression from these profiles distinguished lithotrophy and other rock-associated genes which were highly expressed in cells grown on rocks. Aims: This project focused on four primary aims: 1) Show that B. saxobsidens cells will colonize and respire rock types beyond the sandstones they were initially isolated from. 2) Identify the rock associated genes and operons that are expressed while B. saxobsidens cells colonize and respire rock. 3) Assess differential gene expression of B. saxobsidens transcriptomes from growth on three different rock types. 4) Establish a B. saxobsidens RNAseq informed metabolic-network resource and compare rock-associated genes across a Geodermatophilaceae STAG phylogeny. Results: The tetrazolium bioassay indicated that B. saxobsidens respired 7 of the 14 different rock types tested to varying degrees. Cell growth led to decreased sample pH which indicates acid excretion is part of the rock degradation cascade which confirmed previous observations. No single or synergized elemental composition was ...